2023
DOI: 10.2188/jea.je20210128
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Fasting Blood Glucose Levels in Middle Age and Cognitive Function in Later Life: The Aichi Workers’ Cohort Study

Abstract: This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process which may lead to differences between this version and the Version of Record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…4,5 A limitation of these studies is that they have not addressed the impact of comorbidities like diabetes at the time of a dementia diagnosis. Diabetes is a risk factor for cognitive decline and dementia, [6][7][8] including in people aged ≥80 years. 9 Older individuals with dementia may be more prone to hyperglycemia and hypoglycemia, mainly because cognitive and physical decline can interfere with medication adherence.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 A limitation of these studies is that they have not addressed the impact of comorbidities like diabetes at the time of a dementia diagnosis. Diabetes is a risk factor for cognitive decline and dementia, [6][7][8] including in people aged ≥80 years. 9 Older individuals with dementia may be more prone to hyperglycemia and hypoglycemia, mainly because cognitive and physical decline can interfere with medication adherence.…”
Section: Introductionmentioning
confidence: 99%
“…DM itself increases the risk of cognitive decline. 13 In Japan, the PLWD receives care from family members and often from long-term care service institutions following the instructions of geriatric physicians or clinicians. There is also a provision of a 'Community-based integrated care system' that has been promoted by the government since 2015.…”
Section: Introductionmentioning
confidence: 99%
“…As we mentioned earlier, appropriate diabetes care for older people with or without dementia would be important to make them active, functioning, and achieving well‐being. DM itself increases the risk of cognitive decline 13 . In Japan, the PLWD receives care from family members and often from long‐term care service institutions following the instructions of geriatric physicians or clinicians.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hands, there are studies showed the opposite ndings. Shimoda et al demonstrated, with the same MoCA measurement, that subjects with diabetes had higher odds ratio to have a MoCA score ≤ 25 (3.2)[37]. However, they did not use linear regression which could quantify the effects of glucose on the MoCA.…”
mentioning
confidence: 99%